Faculty engagement in university-industry research partnerships: findings from a developing country - Kuchumova, G.; Bilyalov, D.; Jonbekova, D. (Studies in Higher Education, Vol. 48, No. 9, 1455-1467, 2023)
University-industry research partnerships are crucial for promoting university entrepreneurship. Faculty as key instigators play a critical role in developing such partnerships. Previous studies demonstrate that faculty engagement depends on a diverse set of factors. Drawing on individual interviews with 76 faculty members from eight public and private universities in Kazakhstan, this study explores factors affecting faculty decisions to engage in industry research partnerships in a developing country. Applying the personal engagement theory, we found that despite perceiving industry partnerships as personally meaningful and being driven by extrinsic and intrinsic motivations, faculty engagement in industry research partnerships in Kazakhstan is limited. The reasons for this are faculty members’ feelings of low safety and availability caused by structural-, organisational- and individual- level barriers and challenges. We also found that some of these barriers and challenges can be more specific for developing countries that tend to have immature economies, suffer from corruption, have limited research capacity, and invest less in research activities.
Keywords: Faculty engagement; university-industry partnerships; research collaboration; entrepreneurship; higher education